Induction motor speed control using varied duty cycle terminal voltage via PI controller - Azwin A.; Ahmed S. (Institute of Physics Publishing, 2023)
Controllers; Electric inverters; Induction motors; Pulse width modulation; Speed control; Control performance; Induction motor model; Induction motor speed control; Motor performance; PI speed controller; Steady state errors; Three phase induction motor; Voltage source inverter; Electric machine control